2013
DOI: 10.1073/pnas.1221834110
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of radiation doses and associated risk from the Fukushima nuclear accident to marine biota and human consumers of seafood

Abstract: Radioactive isotopes originating from the damaged Fukushima nuclear reactor in Japan following the earthquake and tsunami in March 2011 were found in resident marine animals and in migratory Pacific bluefin tuna (PBFT). Publication of this information resulted in a worldwide response that caused public anxiety and concern, although PBFT captured off California in August 2011 contained activity concentrations below those from naturally occurring radionuclides. To link the radioactivity to possible health impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(70 citation statements)
references
References 22 publications
7
61
0
Order By: Relevance
“…Except for the early stage of the accident, such food sources have been screened, and those containing more than 100 Bq/kg of radiocesium (current regulation value) have been eliminated from circulation (14). Recent research, including our own previous study, has shown that doses from the ingestion of radiocesium 5-10 mo after the nuclear accident are considered to be less than those from natural radionuclides such as 40 K and 210 Po (15,16). The inhalation of airborne dust comprising resuspended radioactive deposits represents an additional route of internal exposure (17,18).…”
Section: Significancementioning
confidence: 99%
“…Except for the early stage of the accident, such food sources have been screened, and those containing more than 100 Bq/kg of radiocesium (current regulation value) have been eliminated from circulation (14). Recent research, including our own previous study, has shown that doses from the ingestion of radiocesium 5-10 mo after the nuclear accident are considered to be less than those from natural radionuclides such as 40 K and 210 Po (15,16). The inhalation of airborne dust comprising resuspended radioactive deposits represents an additional route of internal exposure (17,18).…”
Section: Significancementioning
confidence: 99%
“…The calculated internal dose rates for zooplankton in June 2011 were about 10 −4 µGy h −1 , and were, therefore, about 5 times greater than those reported by Fisher et al (2013) for copepods and euphausiids collected 30-600 km off Japan. This difference is mainly due to the fact that in this study the dose rates were calculated for the populations located at 0-30 km from FNPP, where the activity level of 137 Cs was higher.…”
Section: Absorbed Dosementioning
confidence: 58%
“…Nevertheless, there have been debates and great concerns about the risks for people exposed to lower doses since risks are lower and hardly to detect [Akiyama et al, 2012;Fisher et al, 2013;Hasegawa, 2013;Rosen, 2013]. Fukushima prefecture has been conducting thyroid checkups regularly on more than 380,000 residents who were younger than 18 at the time of the disaster.…”
Section: Human Damages and Health Effectsmentioning
confidence: 99%